The Use of Genetics for Reaching a Diagnosis in XY DSD - Faisal Ahmed S. (2023)
Reaching a firm diagnosis is vital for the long-term management of a patient with a difference or disorder of sex development (DSD). This is especially the case in XY DSD where the diagnostic yield is particularly low. Molecular genetic technology is playing an increasingly important role in the diagnostic process, and it is highly likely that it will be used more often at an earlier stage in the diagnostic process. In many cases of DSD, the clinical utility of molecular genetics is unequivocally clear, but in many other cases there is a need for careful exploration of the benefit of genetic diagnosis through long-term monitoring of these cases. Furthermore, the incorporation of molecular genetics into the diagnostic process requires a careful appreciation of the strengths and weaknesses of the evolving technology, and the interpretation of the results requires a clear understanding of the wide range of conditions that are associated with DSD.